2016
DOI: 10.14202/vetworld.2016.1102-1106
|View full text |Cite
|
Sign up to set email alerts
|

Certain hormonal profiles of postpartum anestrus jersey crossbred cows treated with controlled internal drug release and ovsynch protocol

Abstract: Aim:The study was conducted to determine the serum levels of certain hormones in post-partum anestrus cows following treatment with controlled internal drug release (CIDR) and Ovsynch protocol.Materials and Methods:A total of 30 postpartum anestrus cows were divided into three equal groups after thorough gynecoclinical examination. The Group 1 animals received an intravaginal progesterone device on day 0 and 2 ml of prostaglandin F2α (PGF2α) on day of CIDR removal (7th day), Group 2 cows were treated with ovsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…On the Day 5, i.e. on the day of dermal patch removal in Group I, Progesterone level increased as compared with the Day 0, which is comparable as described by Syafnir et al 2011 andJena et al 2016. Hence it could be inferred that ProSync-NF dermal patch has the effect on increasing progesterone level after affixing it on the depilated skin of the animals under treatment.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…On the Day 5, i.e. on the day of dermal patch removal in Group I, Progesterone level increased as compared with the Day 0, which is comparable as described by Syafnir et al 2011 andJena et al 2016. Hence it could be inferred that ProSync-NF dermal patch has the effect on increasing progesterone level after affixing it on the depilated skin of the animals under treatment.…”
Section: Resultssupporting
confidence: 83%
“…In all the reproductive problems in dairy cattle, Anestrus is the most important clinical manifestation that ends up in the substantial losses to the farmers due to reduced calf crop with high treatment cost (Parkinson T J 2019). Anestrus in cattle is generally described as failure of estrus due to functional disturbances in the ovary, many at times characterized by ovary without any of the palpable structures (Ambrose D J 2015, Jena et al 2016, Parkinson T J 2019. In another scenario animal may be regularly cycling but the owner fails to identify the estrus.…”
mentioning
confidence: 99%
“…In recent years, with the increase of average milk yield in the global dairy industry, anestrus in high-producing dairy cows is becoming increasingly problematic (Jena et al. 2016), causing low reproduction rates, extended periods of infertility and calving intervals, with serious consequences to dairy farm economics. Ovarian quiescence has been accepted as the most common cause of anestrus in high-producing cows.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported in Egypt by Saad and EL-Nabawy (2013) who stated that there was a significant increase in serum progesterone at the end of treatment in CIDR-PG treated group, and in the same way Mehni et al (2012) who studied the effect of CIDR on sixty-four lactating Holestian dairy cows reported that there was a significant increase in serum progesterone after end of treatment. Furthermore Jena et al (2016) recorded that there was a significant increase in serum progesterone level of jersey crossbred cows treated with CIDR.…”
Section: The Effect Of Progesterone Device Insertion On Serum Progesteronementioning
confidence: 97%